Irrigation Canal Planning in the Irrigation Area of Pandankrajan Village, Kemlagi District, Mojokerto Regency - Handy Surya Syahputra; Faradlillah Saves (DEARSIP : Journal of Architecture and Civil, 2026)
Pandankrajan Village, Kemlagi District, Mojokerto Regency is an agricultural area that depends on irrigation systems to support land productivity. However, uneven water distribution and the condition of several channels that are still earth canals cause suboptimal water supply to some agricultural fields. This study aims to determine irrigation water requirements, evaluate the capacity of existing channels, and redesign channel dimensions if the existing capacity is insufficient. The methods used include hydrological and hydraulic analyses. Average rainfall was calculated using the Arithmetic Mean method and evapotranspiration using the Penman method, while hydraulic analysis employed the Strickler method to determine flow velocity. The results show that the maximum irrigation water requirement is 0.90 l/s/ha for rice and 0.94 l/s/ha for secondary crops. Channel A is still capable of accommodating the planned discharge, while Channel B requires redesign using a rectangular concrete section with a width of 0.60 m, water depth of 0.26 m, and freeboard height of 0.40 m.